1969
DOI: 10.4319/lo.1969.14.5.0660
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Lake Renewal on Phytoplankton Productivity and Species Composition1

Abstract: Primary production in Marion Lake is inversely related to the rate at which water enters the lake when light intensity is corrected to a standard level. Increased flushing rates reduce the phytoplankton standing crop thereby lowering the total primary productivity in the lake. Thus seasonal variations in rainfall in southwestern British Columbia exert an appreciable influence on the annual productivity pattern of the lake’s phytoplankton. Lake water artificially enclosed within small areas of the lake produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

1973
1973
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 6 publications
4
48
1
Order By: Relevance
“…This supports the widely observed increases in bloom incidents in warm, dry summers in individual eutrophic lakes and reservoirs. The impact of retention time on phytoplankton composition has not been so extensively studied, although it has been demonstrated that small phytoplankton with relatively high reproductive rates tend to dominate lakes or seasons when retention times are low (high wash-out) (Dickman, 1969;Bailey-Watts et al, 1990). Large, bloom-forming cyanobacteria are recognised for their slower reproductive rates compared to many diatoms and small green or flagellate algae (Reynolds, 2006) and the positive linear response to retention time observed in these models fits with this knowledge.…”
Section: Discussionsupporting
confidence: 49%
“…This supports the widely observed increases in bloom incidents in warm, dry summers in individual eutrophic lakes and reservoirs. The impact of retention time on phytoplankton composition has not been so extensively studied, although it has been demonstrated that small phytoplankton with relatively high reproductive rates tend to dominate lakes or seasons when retention times are low (high wash-out) (Dickman, 1969;Bailey-Watts et al, 1990). Large, bloom-forming cyanobacteria are recognised for their slower reproductive rates compared to many diatoms and small green or flagellate algae (Reynolds, 2006) and the positive linear response to retention time observed in these models fits with this knowledge.…”
Section: Discussionsupporting
confidence: 49%
“…In June and July 2007, high water temperature and scarce water renewal, together with a high stability of meteo-climatic conditions, determined hypoxic events on the lake bottom, due to high oxygen demand by the benthic and pelagic systems. High water velocity reduces phytoplankton accumulation by flushing algae outside and by affecting negatively the primary production rates [23,46]. Conversely, Rennella and Quiros [25] found that high water flow leads to a twofold increase in algal biomass in shallow lakes with high nutrient levels, likely due to decreased grazing pressure and improved light availability.…”
Section: Primary Producers and Physico-chemical Characterizationmentioning
confidence: 99%
“…All factors described above might be of secondary importance on planktons' biomass in the reservoir, if considerable plankton standing crop is removed by flushing [50]. If plankton community structure is affected by such flushing and thus residence time of water in the reservoir, we expect that both phytoplankton and zooplankton biomass will decrease during periods of high water discharge and that plankton species with high generation time will be replaced during flooding periods by species with shorter generation time [51] [52].…”
Section: Plankton Distributionmentioning
confidence: 99%